The impact of different coastal locations on the growth and Land suitability tissue culture on the Lampung Coast, Indonesia - Meiyana Maya; Rustiaty Banon; Rahman Rivaie Arief; Minjoyo Herno; Handoko; Basi Dhoe Silfester; Saputra Suryadi (BIO Web of Conferences)
This research was conducted at three different locations in the coastal waters of Lampung Indonesia, namely Hurun, Ruguk, and Pahawang, for one- month (March – April) 2021. The cultivation method used is the Long Line method, consisting of 20 points across four lines, with an initial weight of 50 g of seedlings per planting point. A land suitability analysis was conducted by scoring method (23–45), followed by observation of seaweed growth in each location. The result of observation and assessment of land suitability shows that the waters of Ruguk with a score of 38 and the waters of Hurun with a score of 34 are appropriate criteria for seaweed cultivation while the waters of Pahawang are less suitable criteria by the score of 28. receiving a score of only 28. The growth of seaweed, characterized by weight gain, absolute growth, and specific growth rate, was different among locations. The best results were obtained in Ruguk, which achieved a total production of 26,700 g/m and a daily growth rate per month of 8.54%, followed by Hurun, with a total production of 13,680 g/m, and an average daily growth rate per month of 6.32%. Pahawang had the lowest production yield of 9,900 g/m, with an average daily growth rate per month of 5.35%. The assessment of land suitability analysis is very important in land planning and management so that land use can be sustainable and by local environmental characteristics.